Thomas Wetmore, The Charter and Ordinances of the City of Boston: Together with the Acts of the Legislature Relating to the City, at 142-43 §§ 1-2 (1834) - (:unkn) unknown (General Publisher, 1783)
Be it enacted by the Senate and House of Representatives in General Court assembled and by the authority of the same, That if any person shall take into any dwelling house, stable, barn, out house, ware house, store, shop or other building within the town of Boston, any cannon, swivel, mortar, howitzer, cohorn, or fire arm, loaded with or having gunpowder in the same, or shall receive into any dwelling house, stable, barn, out house, store, ware house, shop, or other building within said town, any bomb, grenade, or other iron shell, charged with, or having gun powder in the same, such person shall forfeit and pay the sum of ten pounds, to be recovered at the suit of the firewards [duties of Firewards transferred to Engineers,] of the said towns, in an action of debt before any court proper to try the same; one moiety thereof, to the use of said Firewards, and the other moiety to the support of the poor of said town of Bost
--
Keywords: POSSESSION